Response of Biology Students toward Online Learning in the Covid-19 Pandemic Era - Masiah Masiah; Sri Nopita Primawati (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
This study aimed to describe student responses toward online learning. The respondents in this study were students of the first semester of the Biology Education Department in academic year 2019/2020, totaling 33 people. The sample in this study used a convenience sampling technique. The data obtained were analyzed descriptively using Microsoft Excel. Research data shows that only 6 percent of students feel happy with online learning, because respondents think that they are more flexible about the time and place of learning. Meanwhile, 91 percent of students stated that they were not happy due to many factors such as being difficult to meet face-to-face with friends and lecturers, requiring a lot of money to buy internet quota and an unstable internet network. Referring to these results, it is very necessary to conduct an evaluation by lecturers and relevant policy makers to support the achievement of maximum learning objectives.